Osmium-mediated oxidative cyclizations: a study into the range of initiators that facilitate cyclization. - Donohoe, T; Wheelhouse, K; Lindsay-Scott, P; Churchill, G; Connolly, M; Butterworth, S; Glossop, P (2009)
A general route to prepare substituted, saturated five-membered heterocycles has been developed. The application of a wide range of starting materials to the osmium-catalyzed oxidative cyclization reaction is described. Diols, hydroxy-amides, hydroxy-sulfonamides, and carbamates all cyclize in moderate to excellent yields to give cis-tetrahydrofurans and pyrrolidines, depending upon the position of the heteroatoms in the starting materials. These cyclizations all proceed with near total selectivity for the cis-heterocycles, and with stereospecific introduction of a hydroxy group adjacent to the ring. Moreover, routes to enantiopure starting materials are described, which give enantiopure products upon cyclization. Catalyst loadings of as low as one mol percent have been successfully employed for this transformation.